Just the Facts: Diagnosing growth plate fractures in the emergency department. Issue 3 (May 2020) - Woods, Rob; Boutis, Kathy
Abstract : A 12-year-old male injured his ankle while playing hockey (Figure 1). His dad reports that he was checked into the boards. His ankle is swollen, but does not appear deformed. His distal neurovascular exam is normal. There is bony tenderness over the lateral malleolus in accordance with the Ottawa Ankle Rules.